Model of Strengthening School and Family Cooperation in Character Development of Students During the COVID-19 Pandemic - Aunurrahman Aunurrahman; Fidyatul Nazhira (STKIP Singkawang, 2022)
This study substantively aims to find a model for continuing the cooperation of schools and parents in character education of students during the pandemi Covid-19 which examines schools in the Aruk Border area, as one of the gates of the Indonesia-Malaysia border in West Kalimantan. To achieve these goals, this research was conducted with an approach through interviews as a data collection technique. Interviews were conducted with principals and teachers at several schools in Aruk as one of the Indonesia-Malaysia border areas in West Kalimantan. Data obtained through subsequent interviews with interactive qualitative analysis techniques. In general, the research can be said that the model strengthens school and family cooperation in developing the character of students during the pandemi Covid-19 at schools in the Aruk border area of West Kalimantan, which focuses more on collaborative programs that are integrated with bold learning programs. In general, schools strengthen cooperation between schools and parents for the development of student character in a unitary learning program that is bold and inseparable in particular. In its implementation, increasing student character development cooperation during the covid pandemic is faced with many obstacles, mainly stemming from limited network access, the absence of special school programs to strengthen the character during the pandemic and the lack of readiness of parents to carry out a fairly heavy role during the pandemic.